A response to the perception of the severity of medical error and the level of clinical seniority - Farag S (Advances in Medical Education and Practice, 2018)
Soma Farag  Medical Department at Imperial College, London University, London, UK I read with interest the study by Khan and Arsanious1 which gave insight into the perception of the severity of medical errors of practitioners of different grades and believed that there is much to be gained from it. Medical error in the duration of one’s career is inevitable. The General Medical Council (GMC) advocates a Duty of Candor,2 which means to be open and honest when medical errors occur. In order to successfully explain what went wrong to patients and their relatives or seniors, one should first acknowledge that one has made the error and have an accurate perception of how severe this was.  Authors’ reply Iqbal Khan,1 Meret Arsanious2 1Northampton General Hospital NHS Trust, Northampton, UK; 2Epsom and St Helier University Hospitals NHS Trust, London, UK  We would like to thank the colleague for the helpful comments and agree with the observation that there should be better communication between teams to ascertain individual perception of the severity of an error and its impact on the patient. Across the UK, there is much effort in training medical students and junior doctors to prevent all errors which especially includes prescribing errors.  View the original paper by Khan and Arsanious and colleagues.